THE EFFECT OF COMBINATION OF TURMERIC EXTRACT (Curcuma domestica Val.) AND HONEY ON GASTRIC ULCERS IN MICE (Mus musculus) DUE TO KETOPROFEN ADMINISTRATION MICROSCOPICALLY - Sianturi, Novita Angraini; Repi, Rudi; Tengker, Anita C. C. (Indonesian Biodiversity Journal, 2025)
Gastric ulcers are one of the common side effects that occur as a result of using non-steroidal anti-inflammatory drugs (NSAIDS) such as ketoprofen. The combination of turmeric extract (Curcuma domestica Val) and honey has the potential as an alternative therapy due to its antioxidant, anti-inflammatory, and cytoprotective properties. This research aims to evaluate the effects of the combination of these two substances on gastric ulcers in mice induced by ketoprofen microscopically. To determine the effect of a combination of turmeric extract and honey on the histopathological profile of stomach ulcers in mice (Mus musculus) induced by ketoprofen. This study used an experimental method with a completely randomized design. Mice were divided into several groups, namely the negative control group (without treatment), positive control (ketoprofen without therapy), and the treatment group that was given a combination of turmeric extract and honey with varying doses. Gastric ulcers are induced by administration of ketoprofen, followed by microscopic observation of gastric mucosal damage. The data was analyzed statistically to see significant differences between groups. Histopathological observations show that the group given a combination of turmeric extract and honey experienced a significant reduction in the level of gastric mucosal damage compared to the positive control group. The combination is capable of reducing inflammation, necrosis, and accelerating tissue regeneration. The combination of turmeric extract and honey is effective in reducing gastric ulcers in mice induced by ketoprofen microscopically. This research supports the potential use of both natural substances as adjuvant therapy to prevent or address gastric damage caused by NSAIDS.